Evaluation of HIV-1 neutralizing and binding antibodies in maternal-infant transmission in Thailand - Lindsay Wieczorek (2020)
© 2020 Elsevier Inc. Despite anti-retroviral therapy (ART) interventions for HIV+ pregnant mothers, over 43,000 perinatal infections occur yearly. Understanding risk factors that lead to mother-to-child transmission (MTCT) of HIV are critical. We evaluated maternal and infant plasma binding and neutralizing antibody responses in a drug-naïve, CRF01_AE infected MTCT cohort from Thailand to determine associations with transmission risk. Env V3-specific IgG and neutralizing antibody responses were significantly higher in HIV- infants, as compared to HIV+ infants. In fact, infant plasma neutralizing antibodies significantly associated with non-transmission. Conversely, increased maternal Env V3-specific IgG and neutralizing antibody responses were significantly associated with increased transmission risk, after controlling for maternal viral load. Our results highlight the importance of evaluating both maternal and infant humoral immune responses to better understand mechanisms of protection, as selective placental antibody transport may have a role in MTCT. This study further emphasizes the complex role of Env-specific antibodies in MTCT of CRF01_AE HIV.